2016
DOI: 10.1016/j.semarthrit.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis and mortality: A prospective cohort study and systematic review with meta-analysis

Abstract: Objectives: Osteoarthritis (OA) is a leading cause of disability, but the relationship with premature mortality remains uncertain. We aimed to investigate the relationship between OA and mortality from any cause and from cardiovascular disease (CVD).Methods: Electronic literature databases searches were conducted to identify prospective studies comparing mortality in a sample of people with and without OA.Risk of call-cause and CVD-mortality were summarized using adjusted hazard ratios (HRs) for joint-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
102
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 51 publications
(66 reference statements)
1
102
1
5
Order By: Relevance
“…One of the most common causes of years lived with disability are chronic musculoskeletal disorders [8,9]. Osteoarthritis (OA) of the knee is the 11th highest contributor to global disability [10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common causes of years lived with disability are chronic musculoskeletal disorders [8,9]. Osteoarthritis (OA) of the knee is the 11th highest contributor to global disability [10].…”
Section: Introductionmentioning
confidence: 99%
“…Social isolation has been defined as the consequence of a small social network with few social contacts . It has been reported to be associated with poor physical and mental health . Previous literature has suggested there is an association between musculoskeletal pain and social isolation .…”
mentioning
confidence: 99%
“…Previous literature has suggested there is an association between musculoskeletal pain and social isolation . This has been attributed to comorbid disease and physical impairment …”
mentioning
confidence: 99%
“…Veronese et al [8][9][10] performed a meta-analysis of the literature and found that hip or knee OA was associated with increased mortality (HR 1.18[95% CI 1.08-1.28]). 8 This study also found that hip or knee OA was associated with a 21% increase in cardiovascular mortality.…”
mentioning
confidence: 99%
“…Veronese et al [8][9][10] performed a meta-analysis of the literature and found that hip or knee OA was associated with increased mortality (HR 1.18[95% CI 1.08-1.28]). 8 This study also found that hip or knee OA was associated with a 21% increase in cardiovascular mortality. Leyland et al has presented data utilizing an individualized patient-level meta-analysis of 9889 persons from six population based cohort studies, as well as a similar review of 36,884 persons from nine cohorts 9,10 The latter study was presented in the Osteoarthritis Research Society International's white paper to the US Food and Drug Administration in 2016.…”
mentioning
confidence: 99%